Rice OsCASP1 orchestrates Casparian strip formation and suberin deposition in small lateral roots to maintain nutrient homeostasis - Yang, Xianfeng; Xie, Huifang; Weng, Qunqing; Liang, Kangjing; Zheng, Xiujuan; Guo, Yuchun; Sun, Xinli (Frontiers in Plant Science, 2022)
Rice is a semi-aquatic plant with a more complex root structure than Arabidopsis to adapt its growing conditions, where the deposition of different lignin and suberin is crucial for adaptive responses. Our study showed that the appearance time and structure of Casparian strip (CS) in the roots of rice are different from those of Arabidopsis. We also found suberin deposition in the sclerenchyma in wild type roots. CS membrane domain proteins (CASPs) form a transmembrane scaffold to recruit lignin biosynthetic enzymes for CS formation. Rice CASP1 is highly similar to AtCASPs, but its expression is concentrated in small lateral root (SLR) tips and can be induced by salt stress especially in the steles. The loss of OsCASP1 function alters the expression of the genes involved in suberin biosynthesis and the deposition of suberin in the endodermis and sclerenchyma and leads to delayed CS formation and uneven lignin deposition in SLRs. These different depositions may alter nutrient uptake, resulting in ion imbalance in plant, withered leaves, fewer tillers, and reduced tolerance to salt stress. Our findings suggests that OsCASP1 could play an important role in nutrient homeostasis and adaptation to the growth environment.